Student perceptions towards the implementation of higher education’s character education program: Challenges and the role of the academic environment - Mahriyuni; Udasmoro, Wening; Hardini, Tri Indri; Zein, T. Thyrhaya; Syarfina, T. (Research Journal in Advanced Humanities, 2025)
The purpose of this study is to assess students’ understanding of character education, identify their awareness of the importance of this program, and demonstrate its effectiveness and accessibility in higher educational institutions. The descriptive-qualitative approach is employed through case studies at three universities in Medan City, with data collection through questionnaires distributed to 135 students. The interview technique was also used to obtain data. The results show that almost all students understand the concept of character education and the important conceptualization of moral development and ethics in higher education. Students also realize the need for character education programs and see them as an integral part of forming personality and ethics. Furthermore, lecturers and university administrators implement several special exercises for character education, including routines such as reading prayers before and after learning, comparing seats between students and female students, and providing a lesson plan (RPS) and a syllabus containing character values before semester teaching starts. In addition, higher education character education programs are meticulously planned and revised annually by the college through curriculum and policy evaluation to ensure the program remains successful and relevant for students’ future national and international career development.